Neural control by DTC of a permanent magnet synchronous motor powered by a photovoltaic generator - Far Abouelkacem; Chikhaoui Yacine; Ameur Aissa (UNIVERSITY OF LAGHOUAT. FACULTY OF TECHNOLOGY DEPARTMENT OF ELECTROTECHNIC, 2023)
This study focuses on the investigation of neural control by direct torque control of a permanent magnet synchronous motor powered by a photovoltaic generator . The motor was modeled and its characteristics were identified, followed by an exploration of direct torque control and its effectiveness. The next step involved understanding the power source for the motor, which is the photovoltaic generator, including its characteristics and the impact of temperature and illumination on the system. Finally, we provided an overview of the last component of the control system, which is neural control.
Option : Automatic and system